2015
DOI: 10.1002/ccd.26351
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of adjunctive use of endoanchors in the treatment of short neck and pararenal abdominal aortic aneurysms

Abstract: EndoAnchors are an applicable adjunct to EVAR as treatment for short infrarenal neck and pararenal AAAs. Further investigations are needed to determine the durability of this novel application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Several investigators have evaluated the EndoAnchors technique both in the prevention and treatment of endograft migration and type Ia endoleaks to achieve an effective proximal sealing. 1419 The ANCHOR prospective trial included 319 patients at 43 sites in the United States and Europe; 242 (75.9%) had EndoAnchors implanted at the time of the first operation (primary implant), whereas 77 patients were treated for proximal aortic neck complications after EVAR (secondary implant). The authors reported overall procedural success in 279 patients (87.5%), in particular in 217 of 240 (89.7%) in the primary implant arm and in 62 of 77 (80.5%) in the secondary arm.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have evaluated the EndoAnchors technique both in the prevention and treatment of endograft migration and type Ia endoleaks to achieve an effective proximal sealing. 1419 The ANCHOR prospective trial included 319 patients at 43 sites in the United States and Europe; 242 (75.9%) had EndoAnchors implanted at the time of the first operation (primary implant), whereas 77 patients were treated for proximal aortic neck complications after EVAR (secondary implant). The authors reported overall procedural success in 279 patients (87.5%), in particular in 217 of 240 (89.7%) in the primary implant arm and in 62 of 77 (80.5%) in the secondary arm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified a direct association between short proximal aortic necks and EVAR failure, i.e., presence of endoleaks. 6 Special techniques are therefore needed to solve these complex cases.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,13,14 Moreover, EndoAnchors in combination with chimney EVAR (ch-EVAR) procedures have been described only sporadically. 15,16 Currently, midand long-term outcomes after EndoAnchor use is limited to the results from the ANCHOR multicenter registry. [9][10][11]13 Therefore, this study assesses the 2-year clinical outcomes of patients treated with EndoAnchors after EVAR and ch-EVAR in a single high-volume center.…”
Section: Introductionmentioning
confidence: 99%